Authentic Leadership and Organizational Commitment Toward the Employee Performance in Automotive Industry in Indonesia - Fabriza, Chyntia Azzahra; Susanty, Ade Irma (Universitas Proklamasi 45, 2024)
This study investigate the influence of authentic leadership and organizational commitment in encouraging employee performance. The study was conducted based on questionnaires designed for 65 respondents. The data was collected and analyzed using multiple linear regression techniques with IBM SPSS version 29. The results show that authentic leadership and organizational commitment have positive and significant results on employee performance. This indicates that the higher the application of authentic leadership and ownership of organizational commitment, the higher the performance of employees. Authentic Leadership and Organizational Commitment positively and significantly influence Employee Performance both partially and simultaneously.